The GSK-3 Inhibitor CT99021 Enhances the Acquisition of Spatial Learning and the Accuracy of Spatial Memory - Lee, Yeseul; Bortolotto, Zuner A.; Bradley, Clarrisa A.; Sanderson, Thomas M.; Zhuo, Min; Kaang, Bong-Kiun; Collingridge, Graham L. (Frontiers in Molecular Neuroscience, 2022)
Glycogen synthase kinase 3 (GSK-3) is a ser/thr protein kinase that regulates many cellular processes, including synaptic plasticity. Previously, we reported that inhibition of GSK-3 prevents the induction of one of the major forms of synaptic plasticity, N-methyl-D-aspartate receptor (NMDAR)-dependent long-term depression (LTD), in hippocampal slices. In the present study, we have investigated the effects of inhibiting GSK-3 on learning and memory in healthy naïve animals. Systemic administration of a highly selective GSK-3 inhibitor, CT99021, reversibly blocked NMDA receptor-dependent LTD in the CA1 region of the hippocampus in anesthetized adult mice. In behavioral tasks, CT99021 had no effect on locomotor activity, anxiety, hippocampus-dependent contextual fear memory, and hippocampus-dependent reversal learning. However, CT99021 facilitated the rate of learning in the Morris water maze (MWM) and T-maze and enhanced the accuracy of long-term spatial memory in the MWM. These findings suggest that GSK-3 regulates the accuracy of spatial memory acquisition and recall.